Dynamic estimation of the local business environment in support to investment decisions of the top managers - Zagorcheva, Denitsa Petkova; Pavlov, Daniel Yordanov (Serbian Journal of Management, 2020)
Every manager has some investment ideas for business development. Some of the investments are related to a construction of production facilities in new locations and the investors face variety of risks, which even could stop the initial development plans. Many of these risks are due to the lack of reliable data about the business environment in the new areas. Failing the preparation, they would get heavy financial losses. Here comes the science to empower them with proper economic models. The aim of this article is to present how an economic model for estimation of the local business environment can be applied to some Bulgarian cities on the base of the municipality tax system and the local investment policy. Thus the entrepreneurs would be able to compare the business environment in different municipalities, as well as to identify possible dynamics in their trends.